2011
DOI: 10.1128/jvi.01890-10
|View full text |Cite|
|
Sign up to set email alerts
|

The E4orf6/E1B55K E3 Ubiquitin Ligase Complexes of Human Adenoviruses Exhibit Heterogeneity in Composition and Substrate Specificity

Abstract: Although human adenovirus type 5 (Ad5) has been widely studied, relatively little work has been done with other human adenovirus serotypes. The Ad5 E4orf6 and E1B55K proteins form Cul5-based E3 ubiquitin ligase complexes to degrade p53, Mre11, DNA ligase IV, integrin ␣3, and almost certainly other targets, presumably to optimize the cellular environment for viral replication and perhaps to facilitate persistence or latency. As this complex is essential for the efficient replication of Ad5, we undertook a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 55 publications
8
66
1
Order By: Relevance
“…Previous work by our group and others has shown that a heterogeneity exists in Cullin binding among human adenovirus species (19,20). Whereas Ad5, representing species C, Ad34 (species B2), Ad9 (D), and Ad4 (E) bind essentially only Cul5, Ad12 (A) and Ad40 (F) bind essentially only Cul2.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Previous work by our group and others has shown that a heterogeneity exists in Cullin binding among human adenovirus species (19,20). Whereas Ad5, representing species C, Ad34 (species B2), Ad9 (D), and Ad4 (E) bind essentially only Cul5, Ad12 (A) and Ad40 (F) bind essentially only Cul2.…”
mentioning
confidence: 80%
“…Cul2 was knocked down in H1299 cells (19) by transfection with a plasmid DNA carrying short hairpin RNA (shRNA) against Cul2. The sequence for the shRNA was inserted between EcoRI and BglII sites of the pcDNA3 plasmid: 5=-A GCACCTGAACTGCTTGCT TTCAAGAGA AGCAAGCAGTTCAGG TGCT TTTTT-3=, with the hairpin listed in bold.…”
Section: Methodsmentioning
confidence: 99%
“…In HAdV-infected cells, E1B-55K and E4-34K form a complex with Cul-5 or Cul-2-containing E3 ubiquitin ligases to degrade cellular substrates such as p53. 4,5,9 However, this virus-commandeered E3 ligase may not play a major role in degrading Mdm2 and Mdm4, as both are efficiently degraded in cells infected with a dl1520 mutant virus that does not produce E1B-55K (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…5,6,9 Similarly, Cul5 NTD expression failed to stabilize Mdm2 and Mdm4 in Ad12-infected cells. In contrast, in Ad5-infected cells, Cul5 NTD expression resulted in reduced levels of Mdm2 (Fig.…”
Section: Shrna-mediated Knockdown Of Mdm2 and Mdm4 Augmentsmentioning
confidence: 97%
See 1 more Smart Citation